73.5k views
3 votes
Simplify 2x^2(-3x^2)^3

User Afrischke
by
5.9k points

2 Answers

2 votes

Answer:


-54x^(8)

Explanation:


2x^(2) (-3x^(2) )^(3)

We first carry through the cube.


-3^(3) x^(2*3)


-3^(3) = -27
x^(2*3) = x^(6)

Now we have
2x^(2) (-27x^(6) )

2 * - 27 = -54


x^(2) *x^(6) = x^(8)


-54x^(8)

User Sloneorzeszki
by
5.0k points
5 votes

Answer:


-54x^8

Explanation:


2x^(2)(-3x^2)^3\\\\2x^2((-3)^3(x^(2*3)))\\\\2x^2(-27x^6)\\\\2(-27)(x^(2+6))\\\\-54x^8

User Zoran Pavlovic
by
5.1k points